Gold-nanoparticles microfiber saturable absorber for mode-locked erbium-doped fiber laser - Lau, Kuen Yao; Noor Zirwatul Ahlam, Naharuddin; Abas, A. F.; Alresheedi, Mohammed Thamer; N. H., Zainol Abidin; Mohd Adzir, Mahdi (Institute of Electrical and Electronics Engineers Inc., 2022)
We demonstrate the generation of 743 fs soliton pulses in erbium-doped fiber laser employing gold-nanoparticles saturable absorber. The mode-locking operation is achieved with gold-nanoparticles/polydimethyl-siloxane composite coated on a microfiber with 10\\mu m}$. waist diameter, indicating the availability of fabricated saturable absorber for pulsed operation in 1.55\\mu m}$ spectral range.